Nigeria's Democracy: The Trilemma of Herdsmenism, Terrorism and Vampirism. - Ojo, Emmanuel Oladipo (Journal of Pan African Studies, 2018)
Since the 'invention' of democracy by the Greek City States in the first half of the 5th Century B.C. and its popularisation after the American War of Independence; democracy has remained the most famous form of government. Indeed, today, the presence or absence of democracy in a country seems to be the 'standard' by which such a country is measured -- while countries that practice democracy are patted on the back; those that do not are petted with all sorts of negative descriptions and catogorisations. This outward approval or disapproval has taken the centre stage to the extent that little or no attention has been paid to the analysis of the content and context of a country's democracy. This study examines the content and context of Nigeria's democracy with specific reference to its 'trilema' and argues that Nigeria's democracy is assailed by herdsmenism, terrorism and vampirism.